Mathematical programming theory and methods. - Sinha, Satyabroto (Oxford : Elsevier Science Ltd., 2005)
Mathematical Programming, a branch of Operations Research, is perhaps the most efficient technique in making optimal decisions. It has a very wide application in the analysis of management problems, in business and industry, in economic studies, in military problems and in many other fields of our present day activities. In this keen competetive world, the problems are getting more and more complicated ahnd efforts are being made to deal with these challenging problems. This book presents from the origin to the recent developments in mathematical programming. The book has wide coverage and is self-contained. It is suitable both as a text and as a reference. * A wide ranging all encompasing overview of mathematical programming from its origins to recent developments * A result of over thirty years of teaching experience in this feild * A self-contained guide suitable both as a text and as a reference.
Introduction; MATHEMATICAL FOUNDATIONS; Basic Theory of Sets and Functions; Vector Spaces; Matrices and Determinants; Linear Transformations and Rank; Quadratic Forms and Eigenvalue Problems; Systems of Linear Equations and Linear Inequalities; Convex Sets and Convex Cones; Convex and Concave Functions; LINEAR PROGRAMMING; Linear Programming Problems; Simplex Method: Initial Basic Feasible Solution; Degeneracy in Linear Programming; The Revised Simplex Method; Duality in Linear Programming; Variants of the Simplex Method; Post-Optimization Problems: Sensitivity Analysis and Parametric Programming; Bounded Variable Problems; Transportation Problems; Assignment Problems; The Decomposition Principle for Linear Programs; Polynominal Time Algorithms for Linear Programming; NONLINEAR AND DYNAMIC PROGRAMMING; Nonlinear Programming; Quadratic Programming; Methods of Nonlinear Programming; Duality in Nonlinear Programming; Stochastic Programming; Some Special Topics in Mathematical Programming; Dynamic Programming; Bibliography; Index.
Keywords: Programming (Mathematics).; Electronic books